The impact of HR practices and trust in management on Perceived Organizational Support (POS) in Malaysian universities - Yeap, Marvin Ke Ding; Thye, Mei Teng; Tan, Jia Wen; Chong, Chun Hui; Au, Weng Chee (2020)
Organizational behavior recognizes the importance of perceived organizational support in affecting employees' work commitment and will directly affect company performance. However, the studies that investigates the impact on perceived organizational support are few. This research aims to address this gap. Higher education industry becomes a significant industry in Malaysia and academic staff are viewed as one of the most important assets in this context. This research looked at the extent to which examines the impact of human resources practices and trust in management on perceived organizational support in Malaysian universities. This study adopted quantitative research design. The questionnaire distributed to the academic staff in Perak universities through Google form. The data collected from 153 respondents and the Cronbach’s Alpha reliability test of the independent variables and dependent variable are analysed by SPSS software. The Pearson Correlation Coefficient Analysis and Multiple Regression Analysis are used to test the relationship between independent variables and dependent variables as well. Results revealed that participation in decision making, fairness of rewards, growth opportunity and trust in management was positively and significantly related to perceived organizational support. Findings, theoretical and managerial implications, limitation of study, and the recommendation of future research are discussed.